2020
DOI: 10.1071/cp18357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protodioscin content on digestibility and in vitro degradation kinetics in Urochloa brizantha cultivars

Abstract: Five cultivars of Urochloa brizantha (Hochst. ex A.Rich.) R.D. Webster (syn. of Brachiaria brizantha) were evaluated for nutritional value and an anti-nutritional factor (protodioscin), in order to determine whether protodioscin content was correlated with reduced feed quality. We evaluated cvv. Arapoty, Paiaguas, Xaraes, Marandu and Piata and grouped the results into summer, autumn, winter and spring seasons. Protodioscin content and chemical composition of leaves, in vitro digestibility and cumulative gas pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Some researchers have used nonlinear models to study the kinetics of in vitro gas production (FARIAS et al, 2011;VELHO et al, 2014;TEIXEIRA et al, 2016;GOMES et al, 2017), especially the Gompertz, Richards, Groot and monomolecular models. However, the two-compartment logistic model, proposed by PELL & SCHOFIELD (1993), has been widely used to estimate the in vitro gas production of feedstuffs and diets for ruminants (OLIVO et al, 2017;DIAZ et al, 2018;SOUZA et al, 2018;OLIVEIRA et al, 2017;LEAL et al, 2020. Nevertheless, VELHO et al (2014) warned that a single model should not be used indiscriminately for all types of feed; rather, it is essential that different models be evaluated for each experimental situation.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have used nonlinear models to study the kinetics of in vitro gas production (FARIAS et al, 2011;VELHO et al, 2014;TEIXEIRA et al, 2016;GOMES et al, 2017), especially the Gompertz, Richards, Groot and monomolecular models. However, the two-compartment logistic model, proposed by PELL & SCHOFIELD (1993), has been widely used to estimate the in vitro gas production of feedstuffs and diets for ruminants (OLIVO et al, 2017;DIAZ et al, 2018;SOUZA et al, 2018;OLIVEIRA et al, 2017;LEAL et al, 2020. Nevertheless, VELHO et al (2014) warned that a single model should not be used indiscriminately for all types of feed; rather, it is essential that different models be evaluated for each experimental situation.…”
Section: Introductionmentioning
confidence: 99%
“…The content of protodioscin-the main saponin associated with intoxication and used as an indicator of photosensitization in animals (Lelis et al, 2018)-in the cultivars was low when compared with those described in studies with cultivars of the genus Brachiaria (Faccin et al, 2014;Porto et al, 2013;Leal et al, 2016Leal et al, , 2020. In Brachiaria spp., Melo et al (2018) found that protodioscin levels between 3 and 13 g/kg DM caused intoxication in lactating lambs.…”
Section: Chemical Compositionmentioning
confidence: 84%
“…Protodioscin, a saponin present in plants of the Brachiaria genus, may cause liver lesion and, subsequently, photosensitization (Riet-Correa et al, 2011, Lima et al, 2015. Leal et al (2020) observed the protodioscin contents of five Brachiaria brizantha cultivars: arapoty, paiaguas, xaraes, and marandu palisadegrass, and piata throughout the year in all seasons. All grasses showed the highest protodioscin contents during autumn, ranging from 5.6 g kg -1 in the spring to 19.2 g kg -1 in the autumn.…”
Section: Introductionmentioning
confidence: 96%